Carbon composite rod-like multi-cavity structure FePSe3 composite material as well as preparation method and application thereof

By using carbon composite rod-shaped multi-cavity structure FePSe3 composite material in sodium ion battery electrode material, the problems of insufficient conductivity, rate performance and cycle stability of the electrode material are solved, and efficient conductivity and good cycle stability of the material are achieved.

CN119542417APending Publication Date: 2025-02-28FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311118465.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing sodium ion battery electrode materials have shortcomings in terms of kinetic reaction speed, specific capacity and cyclic stability, especially the conductive performance, rate performance and cyclic stability need to be improved.

Method used

The carbon composite rod-shaped multi-cavity structure FePSe3 composite material is used to improve the conductivity and electrochemical properties of the material by confining FePSe3 nanoparticles in the carbon layer and constructing a rod-shaped multi-cavity structure. The preparation method of this material includes heating the iron salt, organic ligand and solvent under sealed conditions to obtain the MIL88A precursor, then heating in a reducing atmosphere to obtain the iron element, and finally calcined in an inert atmosphere react with the selenium source and the phosphorus source to form a carbon composite rod-shaped multi-cavity structure FePSe3 composite material.

Benefits of technology

The conductive and rate performance of FePSe3 material is improved, the volume expansion problem is alleviated, and the cycle stability is significantly improved, so that the electrochemical performance of sodium ion batteries reaches an excellent level.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542417A_ABST
    Figure CN119542417A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon composite rod-like multi-cavity structure FePSe3 composite material as well as a preparation method and application thereof. The composite material is a rod-shaped body with a multi-cavity structure formed by wrapping FePSe3 nanoparticles with a carbon material layer. The FePSe3 nanoparticles are limited in the carbon layer to form the rod-like multi-cavity structure, and the formed rod-like multi-cavity structure not only improves the conductivity of FePSe3 and obtains excellent rate capability, but also can relieve the problem of volume expansion of FePSe3 in the cycle process and obtains good cycle stability; when the composite material is used as a sodium battery negative electrode material, the rod-like multi-cavity structure is beneficial to permeation of electrolyte, the diffusion path of sodium ions is shortened, and the electrochemical performance of the sodium battery negative electrode material can be improved. The method is simple to operate, high in product yield and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of material technology, and in particular relates to a carbon composite rod-shaped multi-cavity structure FePSe3 composite material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in electric vehicles, green power grids, etc. However, the shortage of lithium resources has led to rising lithium prices and high costs, so scientists are in urgent need of developing new long-life energy storage devices with low cost and high performance. Compared with lithium, metal sodium in the same main group has similar physical and chemical properties, and is abundant in resources and low in price, so sodium-ion batteries have come into people's view. However, the radius of sodium ions is larger than that of lithium, which leads to slower insertion and extraction of sodium ions in electrode materials, and it is easy to cause damage to the structure of active materials, affecting the cycle stability of the battery. Therefore, the main problem of sodium-ion batteries at present is to develop electrode materials with fast kinetic response, high specific capacity and good cycle stability.

[0003] Recently, iron-based phosphides have the advantages of abundant resources and low cost, but they are used in sodium-ion batteries with low capacity, unstable cycles, poor conductivity, and low coulombic efficiency. Due to the large radius of selenium atoms, the interlayer spacing of iron phosphide can be effectively expanded, which is conducive to the deintercalation of sodium ions and accelerates the kinetic reaction. Selenium doping causes lattice distortion of iron phosphide, produces a large number of defects, increases sodium storage sites, and is conducive to improving the capacity of sodium-ion batteries.

[0004] Common physical methods for preparing FePSe3 include magnetron sputtering, stripping and solid-phase reaction. Traditional chemical methods include hydrothermal method, sol-gel method and chemical vapor deposition method. However, in previous synthesis methods, the use of a single solid-phase reaction often takes a long time and requires a high temperature. Therefore, it is urgent to develop a synthesis method that is less time-consuming and can be widely used for this type of material. Summary of the invention

[0005] In view of this, the present invention provides a carbon composite rod-shaped multi-cavity structure FePSe3 composite material and its preparation method and application, the main purpose of which is to solve the technical problems that need to be improved, such as the conductivity, rate performance, cycle stability and volume expansion of battery electrode materials.

[0006] On the one hand, the present invention provides a carbon composite rod-shaped multi-cavity structure FePSe3 composite material, wherein the composite material is a carbon material layer that wraps FePSe3 nanoparticles inside to form a rod-shaped body with a multi-cavity structure.

[0007] Optionally, the lattice spacing of the FePSe3 nanoparticles is 0.28 nm, corresponding to the (11-3) crystal plane.

[0008] Optionally, the composite material is in the form of porous carbon nanorods, and FePSe3 nanoparticles are encapsulated in the porous carbon nanorods.

[0009] The FePSe3 nanoparticles of the present invention are confined in a multi-cavity structure and are coated with a carbon layer on the surface, thereby obtaining a FePSe3 nanomaterial with a carbon composite rod-shaped multi-cavity structure; this composite nanomaterial structure will greatly improve the electrical conductivity of the material, while the rod-shaped multi-cavity structure can well inhibit the volume expansion of FePSe3, thereby obtaining excellent electrochemical properties.

[0010] In a second aspect, the present invention provides a method for preparing the above-mentioned carbon composite rod-shaped multi-cavity structure FePSe3 composite material, the method comprising the following steps:

[0011] S1: Raw materials containing iron salt, organic ligand and solvent are mixed and heated under closed conditions to obtain MIL88A precursor;

[0012] S2: the MIL 88A precursor in step S1 is heated and cracked in a reducing atmosphere to obtain an iron element derived from the MIL 88A precursor;

[0013] S3: The iron element, selenium source and phosphorus source derived from the MIL 88A precursor in step S2 are calcined and cooled in an inert atmosphere to obtain a carbon composite rod-shaped multi-cavity structure FePSe3 composite material.

[0014] Optionally, in step S1, the mixing ratio of the iron salt, the organic ligand and the solvent is 2-4 g: 0.3-1.0 g: 100-150 mL.

[0015] Optionally, in step S1, the mixing ratio of the iron salt, the organic ligand and the solvent is 2-3 g: 0.5-0.8 g: 100-130 mL.

[0016] Optionally, in step S1, the iron salt is selected from salts containing ferric nitrate or ferric chloride; the organic matter is selected from fumaric acid; and the solvent is selected from deionized water or dimethylformamide.

[0017] Optionally, the iron salt is selected from ferric nitrate nonahydrate or ferric chloride hexahydrate.

[0018] Optionally, in step S1, the temperature of the heating reaction is 100-120° C., and the time of the heating reaction is 4-8 hours.

[0019] Optionally, in step S1, the temperature of the heating reaction is selected from any value of 100°C, 105°C, 110°C, 115°C, 120°C, or a range between any two of them; the time of the heating reaction is selected from any value of 4, 5, 6, 7, 8h, or a range between any two of them.

[0020] Optionally, in step S2, the temperature of the heating and cracking is 480-520°C, and the time of the heating and cracking is 1-3 hours.

[0021] Optionally, in step S2, the temperature of the heating cracking is selected from any value of 480°C, 490°C, 500°C, 510°C, 520°C, or a range between any two of them; the time of the heating cracking is selected from any value of 1h, 1.5h, 2h, 2.5h, 3h, or a range between any two of them.

[0022] Optionally, in step S2, the heating and cracking are carried out under the reducing atmosphere containing hydrogen.

[0023] Optionally, in step S3, the mass ratio of the iron element derived from the MIL 88A precursor, the selenium source and the phosphorus source is 50-60:200-240:700-780.

[0024] Optionally, in step S3, the mass ratio of the iron element derived from the MIL 88A precursor, the selenium source and the phosphorus source is 52-58:210-230:720-760.

[0025] Optionally, in step S3, the selenium source is selected from selenium powder; and the phosphorus source is selected from phosphate-containing substances.

[0026] Optionally, the phosphorus source is selected from sodium phosphate monohydrate.

[0027] Optionally, in step S3, the calcination temperature is 420-480° C., and the calcination time is 1-3 hours.

[0028] Optionally, in step S3, the calcination temperature is selected from any value of 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, or a range between any two of them; the calcination time is any value of 1, 1.5, 2, 2.5, 3h, or a range between any two of them.

[0029] Optionally, the heating and cracking process in step S2 and the calcination process in step S3 are both carried out in a tubular furnace, and the heating rate in the tubular furnace is 1 to 3°C / min; the reducing atmosphere in step S2 contains hydrogen and argon, and the inert gas in step S3 is argon.

[0030] Optionally, in step S1, the iron salt and the solvent are mixed and ultrasonically treated to obtain solution A; the organic matter and the solvent are stirred and mixed at a constant temperature of 60 to 80°C to obtain solution B; the solution A is added dropwise to the solution B to obtain solution C, and the solution C is placed in a polytetrafluoroethylene reactor, placed in an oven at a temperature of 100 to 120°C for 4 to 8 hours, cooled to room temperature, and centrifuged to obtain the MIL 88A precursor.

[0031] Optionally, in step S3, the iron element derived from the MIL 88A precursor is placed in the center of a tubular furnace in an argon atmosphere, and the selenium source and the phosphorus source are placed upstream of the tubular furnace. The temperature is increased to 420-480°C at a heating rate of 2°C / min and kept warm for 1-3 hours. After the reaction is complete, it is naturally cooled to room temperature to obtain the carbon composite rod-shaped multi-cavity structure FePSe3 composite material.

[0032] The present invention uses MIL 88A precursor as an iron source, selenium powder and sodium hypophosphite as selenium sources and phosphorus sources. MIL 88A can be prepared in large quantities, and each batch can obtain gram levels. The MIL 88A precursor will produce a rod-shaped multi-cavity structure during the high-temperature pyrolysis process, and the multi-cavity structure will be more obvious in the subsequent selenium phosphating process. FePSe3 nanoparticles will be confined in the multi-cavity structure, and the surface will be wrapped with a carbon layer to obtain a carbon composite rod-shaped multi-cavity FePSe3 nanomaterial; this composite nanomaterial structure will greatly improve the electrical conductivity of the material, and at the same time, the rod-shaped multi-cavity structure can well inhibit the volume expansion of FePSe3, thereby obtaining excellent electrochemical performance. In addition, this method has a simple production process, is environmentally friendly, has a high product yield, low production cost, and is easy to commercialize.

[0033] In a third aspect, the present invention provides a carbon composite rod-shaped multi-cavity structure FePSe3 composite material, which is prepared by the above method.

[0034] In a fourth aspect, the present invention provides a carbon composite rod-shaped multi-cavity structure FePSe3 composite material prepared by the above preparation method or the use of the above composite material in a sodium ion battery.

[0035] In a fifth aspect, the present invention provides an electrode sheet, wherein active material powder, a conductive agent and a binder are ground and added with water to form a slurry, the slurry is coated on a copper foil, and then the slurry is placed in a vacuum drying oven at 60 to 80° C. for 20 to 30 hours to obtain an electrode sheet;

[0036] Among them, the active material powder is the carbon composite rod-shaped multi-cavity structure FePSe3 composite material prepared by the above preparation method or the above composite material.

[0037] In a sixth aspect, the present invention provides a sodium ion button battery, comprising an electrode sheet and a counter electrode; the electrode sheet is the above-mentioned electrode sheet.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] (1) The present invention provides a carbon composite rod-shaped multi-cavity structure FePSe3 nanoparticle composite material, which confines FePSe3 nanoparticles in a carbon layer and constructs a rod-shaped multi-cavity structure. The rod-shaped multi-cavity structure not only improves the conductivity of FePSe3 and obtains excellent rate performance, but also alleviates the volume expansion problem of FePSe3 during the cycle process and obtains good cycle stability.

[0040] (2) When the carbon composite rod-shaped multi-cavity structure FePSe3 nanoparticle composite material provided by the present invention is used as a negative electrode material for a sodium battery, its rod-shaped multi-cavity structure is conducive to the penetration of the electrolyte, reduces the diffusion path of sodium ions, and can greatly improve the electrochemical performance of the negative electrode material for the sodium battery.

[0041] (3) The present invention provides a method for preparing a composite material, which has a simple production process, is environmentally friendly, has a high product yield, low production cost, and is easy to commercialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The X-ray diffraction pattern of the product obtained by implementing the preparation process of the present invention;

[0043] Figure 2 This is a field emission scanning electron microscope image of the product obtained by implementing the preparation process of the present invention;

[0044] Figure 3 The transmission electron microscope image of the product obtained by implementing the preparation process of the present invention;

[0045] Figure 4 This is a high-magnification transmission electron microscope image of the product obtained by implementing the preparation process of the present invention;

[0046] Figure 5 The selected area diffraction electron microscope image of the product obtained by implementing the preparation process of the present invention;

[0047] Figure 6 The charge and discharge performance curve diagram of the electrode material prepared by the preparation process of the present invention;

[0048] Figure 7 The electrochemical cycle performance diagram of the electrode material prepared by the preparation process of the present invention;

[0049] Figure 8 It is an electrochemical rate performance diagram of the electrode material prepared by the preparation process implemented in the present invention. DETAILED DESCRIPTION

[0050] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.

[0051] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.

[0052] Example 1 (Preparation of Carbon Composite Rod-Shaped Multi-Cavity Structure FePSe3 Composite Material)

[0053] (1) Preparation of precursor:

[0054] 2.69 g of ferric nitrate nonahydrate was added to 25 mL of deionized water, and ultrasonic treatment was performed for 10 minutes, which was recorded as solution A; 0.7 g of fumaric acid was added to 100 mL of deionized water, and stirred at a constant temperature of 70°C for 15 minutes, which was recorded as solution B; solution A was slowly added to solution B, and after stirring for 20 minutes, the mixture was transferred to a polytetrafluoroethylene reactor, placed in an oven at 110°C for 6 hours, cooled to room temperature, and centrifuged and dried to obtain a MIL 88A precursor;

[0055] (2) Preparation of intermediate products:

[0056] The MIL 88A precursor prepared in step (1) is placed in a tube furnace with a mixed atmosphere of hydrogen and argon, heated to 500° C. at a heating rate of 2° C. / min, kept at this temperature for 2 h, and naturally cooled to room temperature after the reaction is complete, to obtain an iron element derived from the MIL 88A precursor;

[0057] (3) Calcination process:

[0058] 55 mg of iron derived from the MIL 88A precursor prepared in step (2) is placed in the center of a tubular furnace in an argon atmosphere, and 220 mg of selenium powder and 740 mg of sodium hypophosphite monohydrate are placed upstream of the tubular furnace. The temperature is increased to 450°C at a heating rate of 2°C / min and kept at this temperature for 2 hours. After the reaction is complete, the mixture is naturally cooled to room temperature to obtain a carbon composite rod-shaped multi-cavity structure FePSe3 composite material.

[0059] The composite material prepared in Example 1 was characterized as follows: Figure 1 to Figure 5 shown.

[0060] The present invention Figure 2The SEM images show that the MIL-88A precursor maintains a complete rod-shaped multi-cavity structure after high-temperature carbonization and selenium phosphating treatment.

[0061] The present invention Figure 3 The TEM images show that the multi-cavity structure with internal voids is constructed by core-shell FePSe3 encapsulated in porous carbon nanorods, and the FePSe3 nanoparticles are well encapsulated in the carbon framework; among them, the carbon layer wrapped with FePSe3 nanoparticles can effectively prevent the FePSe3 nanoparticles from being directly exposed to the electrolyte, thereby improving the conductivity of the composite material.

[0062] The present invention Figure 4 The high-magnification transmission electron microscope image shows that the light gray is the carbon layer material, which is in the outer layer. The slightly darker color wrapped by the outer layer material is the inner layer material, and the inner layer is FePSe3 nanoparticles. The lattice spacing of FePSe3 is 0.283nm between the two horizontal lines in the figure.

[0063] The present invention Figure 5 The selected area electron diffraction (SAED) pattern shows multiple diffraction rings, proving that the multi-cavity FePSe3 nanostructure is polycrystalline.

[0064] In step (2) of the present invention, the MIL-88A precursor initially forms a multi-cavity structure after high-temperature pyrolysis. This is because the organic framework of the MIL-88A precursor collapses at high temperature, forming metallic iron and graphitized carbon shells, and a multi-cavity structure appears.

[0065] In the process of selenyl phosphating in step (3) of the present invention, the multi-cavity structure formed by the iron element derived from the MIL 88A precursor, selenium powder and sodium hypophosphite are decomposed at high temperature to obtain gaseous hydrogen selenide and phosphine. The phosphine and hydrogen selenide gases further expand the cavity structure. The second high-temperature cracking organic framework collapses more obviously, and the cavity structure is significantly formed under the joint action of phosphine and hydrogen selenide.

[0066] Example 2 (Assembly of sodium ion button cells)

[0067] The carbon composite rod-shaped multi-cavity structure FePSe3 composite material prepared in Example 1 was artificially prepared into a button-type sodium ion battery, and the specific steps were as follows: the active material powder, the conductive agent (Ketjen black) and the binder (sodium carboxymethyl cellulose CMC) were evenly ground in a mass ratio of 8:1:1, and a small amount of deionized water was added to make a slurry, the slurry was applied on a copper foil with a diameter of 12 mm, and then it was kept at 70°C in a vacuum drying oven for 24 hours to obtain an electrode sheet; finally, the electrode sheet was assembled into a sodium ion button battery in a glove box with metallic sodium as the counter electrode.

[0068] By the present invention Figure 6It can be seen that at 0.1A g -1 At a current density of 1.5 %, the first cycle discharge capacity reached 595 mAh g -1 The first coulombic efficiency is above 85%, and the second and fifth cycle charge and discharge curves are almost identical, indicating that this active material has good reversibility.

[0069] By the present invention Figure 7 It can be seen that in 2Ag -1 At a current density of 1000 cycles, the battery capacity is still as high as 339 mAh g -1 .

[0070] By the present invention Figure 8 It can be seen that after the current density is continuously increased, when it returns to the small current density of 0.1A -1 It can also achieve high capacity, up to 530mAh g -1 This indicates that after selenium doping, the electrochemical properties of FePSe3 electrode materials are improved, and this unique rod-shaped multi-cavity structure greatly improves the volume expansion problem caused by the FePSe3 cycle process, thereby achieving excellent sodium storage performance.

[0071] Comparative Example (Solvent-free method)

[0072] 0.112 g of ferrocene Fe(C5H5)2, 0.019 g of red phosphorus, and 0.142 g of selenium powder were mixed under sealed conditions and heated to 600°C for thermal decomposition reaction. The reaction time was 24 hours. After the reaction was completed, it was cooled to room temperature and the product was washed with ethanol to obtain the product.

[0073] Results and characterization: The obtained product is layered hybrid FePSe3 / C nanosheets with a flake-like morphology.

[0074] Electrochemical performance: The sodium ion button cell was assembled in the manner of Example 2, and its electrical performance was measured as follows: - After 50 cycles at a current density of 1, the discharge capacity of the nanosheet was 182.7 mA h g - 1; at 1A g - At a current density of 1, the discharge capacity of the nanosheets was 142 mA h g after 200 cycles. - 1. The rate performance is seriously degraded.

[0075] By comparing the electrical properties of Example 2 and the comparative example, the comprehensive electrical properties of Example 2 of the present invention are much better than those of the comparative example, which indicates that the electrical properties of the material prepared by the comparative example are poor.

[0076] The electrode material of the present invention is a carbon composite rod-shaped multi-cavity structure FePSe3 composite material, which is a FePSe3 particle encapsulated in a carbon material, and has a multi-cavity structure inside, which solves the volume expansion problem of the material during the cycle and improves the sodium storage performance. In contrast, the layered hybrid FePSe3 / C nanosheet of the comparative example is a layered, sheet-like nanomaterial formed by carbon coated on the surface of FePSe3, and there is no multi-cavity structure in the material, so it does not have the problem of solving the volume expansion problem of the composite material during the electrical cycle, which is further not conducive to the sodium storage performance of the material.

[0077] By comparing the preparation methods of Example 1 and Comparative Example 2, step 1 of Example 1 of the present invention is to react iron salts and organic ligands to obtain an organic metal framework material. This material will undergo framework collapse under the high-temperature cracking of step 2 to initially form a carbon-coated iron product with a multi-cavity structure; while Comparative Example 2 uses ferrocene as an iron source and a carbon source, and this material structure is completely different from the organic metal framework structure of the present invention. Ferrocene will form a layered or sheet-like product after high-temperature cracking, and will not form a product with a cavity structure. When it reacts with phosphorus and selenium in the subsequent reaction, a composite material with a stable layered or sheet-like structure is further formed; and when the present invention reacts with phosphorus and selenium on the basis of the initial carbon-coated iron multi-cavity structure obtained in the second step, a composite product with an obvious multi-cavity structure is further formed through a gaseous intermediate product; that is, the raw materials of the present invention are different from those of the comparative example, resulting in different structures of the later products; and the pyrolysis temperature of the material in the solvent-free method of the comparative example reaches 600°C, and the pyrolysis temperature for obtaining a better product needs to reach 24h, and its pyrolysis temperature and time far exceed the pyrolysis conditions of Example 1 of the present invention, which consumes more energy and has a higher cost, and is not conducive to industrial production.

[0078] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A carbon composite rod-shaped multi-cavity structure FePSe3 composite material, characterized in that: The composite material is a rod-shaped body with a multi-cavity structure formed by wrapping FePSe3 nanoparticles in a carbon material layer.

2. According to claim 1, a carbon composite rod-shaped multi-cavity structure FePSe3 composite material is characterized in that: The lattice spacing of the FePSe3 nanoparticles is 0.28 nm, corresponding to the (11-3) crystal plane; Preferably, the composite material is a porous carbon nanorod, and the porous carbon nanorod is encapsulated with FePSe3 nanoparticles.

3. A method for preparing a carbon composite rod-shaped multi-cavity structure FePSe3 composite material according to claim 1 or 2, characterized in that: The method comprises the following steps: S1: Raw materials containing iron salt, organic ligand and solvent are mixed and heated under closed conditions to obtain MIL 88A precursor; S2: the MIL 88A precursor in step S1 is heated and cracked in a reducing atmosphere to obtain an iron element derived from the MIL 88A precursor; S3: The iron element, selenium source and phosphorus source derived from the MIL 88A precursor in step S2 are calcined and cooled in an inert atmosphere to obtain a carbon composite rod-shaped multi-cavity structure FePSe3 composite material.

4. The method for preparing a carbon composite rod-shaped multi-cavity structure FePSe3 composite material according to claim 3, characterized in that: In step S1, the mixing ratio of the iron salt, the organic ligand and the solvent is 2-4 g: 0.3-1.0 g: 100-150 mL; Preferably, in step S1, the iron salt is selected from a salt containing iron nitrate or iron chloride; the organic ligand is selected from fumaric acid; and the solvent is selected from deionized water or dimethylformamide; Preferably, in step S1, the temperature of the heating reaction is 100-120° C., and the time of the heating reaction is 4-8 hours.

5. The method for preparing a carbon composite rod-shaped multi-cavity structure FePSe3 composite material according to claim 3, characterized in that: In step S2, the temperature of the heating and cracking is 480-520°C, and the time of the heating and cracking is 1-3h; Preferably, in step S3, the mass ratio of the iron element derived from the MIL 88A precursor, the selenium source and the phosphorus source is 50-60:200-240:700-800; Preferably, in step S3, the selenium source is selected from selenium powder; the phosphorus source is selected from phosphate-containing substances; Preferably, in step S3, the calcination temperature is 420-480° C., and the calcination time is 1-3 hours.

6. The method for preparing a carbon composite rod-shaped multi-cavity structure FePSe3 composite material according to claim 3, characterized in that: The heating and cracking process in step S2 and the calcining process in step S3 are both carried out in a tubular furnace, and the heating rate in the tubular furnace is 1-3°C / min; the reducing atmosphere in step S2 contains hydrogen and argon, and the inert gas in step S3 is argon; Preferably, in step S1, the iron salt and the solvent are mixed and ultrasonically treated to obtain a solution A; the organic matter and the solvent are stirred and mixed at a constant temperature of 60 to 80°C to obtain a solution B; the solution A is added dropwise to the solution B to obtain a solution C, and the solution C is placed in a polytetrafluoroethylene reactor, placed in an oven at a temperature of 100 to 120°C for 4 to 8 hours, cooled to room temperature, and centrifuged to obtain the MIL 88A precursor.

7. The method for preparing a carbon composite rod-shaped multi-cavity structure FePSe3 composite material according to claim 3, characterized in that: In step S3, the iron element derived from the MIL 88A precursor is placed in the center of a tubular furnace in an argon atmosphere, and the selenium source and the phosphorus source are placed upstream of the tubular furnace. The temperature is increased to 420-480°C at a heating rate of 2°C / min and kept warm for 1-3 hours. After the reaction is complete, it is naturally cooled to room temperature to obtain the carbon composite rod-shaped multi-cavity structure FePSe3 composite material.

8. Use of the carbon composite rod-shaped multi-cavity structure FePSe3 composite material prepared by the preparation method according to any one of claims 3 to 7 or the composite material according to claim 1 or 2 in sodium ion batteries or.

9. An electrode sheet, characterized in that: Grinding active material powder, conductive agent and binder, adding water to prepare slurry, coating the slurry on copper foil, and then placing the copper foil in a vacuum drying oven at 60-80° C. for 20-30 hours to obtain an electrode sheet; Wherein, the active material powder is a carbon composite rod-shaped multi-cavity structure FePSe3 composite material prepared by the preparation method described in any one of claims 3 to 7 or the composite material described in claim 1 or 2.

10. A sodium ion button battery, comprising an electrode sheet and a sodium metal sheet; characterized in that: The electrode sheet is the electrode sheet according to claim 9.